Effectiveness of Youth Mental Health First Aid USA for Social Work Students. (March 2019) - Rose, Theda; Leitch, Judith; Collins, Kathryn S.; Frey, Jodi J.; Osteen, Philip J.
Purpose: Adolescent mental health is a public health priority. Considered an early intervention approach, Youth Mental Health First Aid (YMHFA) trains adults to provide initial assistance to adolescents experiencing a mental health problem or crisis. This study evaluated the effectiveness of the U.S. version of YMHFA (YMHFA-USA) among graduate social work students. Method: A quasi-experimental design ( N = 73; intervention, n = 39; comparison, n = 34), using the Mental Health Beliefs and Literacy Scale, assessed the effectiveness of YMHFA-USA. Outcomes were measured at pretest, posttest, and 5 months in the intervention group. Differences between groups were compared at 5 months. Results: Statistically significant improvements in attitudes, beliefs, self-confidence, and knowledge were observed among intervention group students. At 5 months, these students had significantly better attitudes and greater knowledge and self-confidence than the comparison group. Conclusion: Results indicate YMHFA-USA may improve factors related to master's level social work students' abilities to engage with youth experiencing mental health problems.